Botulinum toxin versus pneumatic dilatation in the treatment of achalasia: a randomised trial. Issue 2 (1st February 1999) - Vaezi, M F; Richter, J E; Wilcox, C M; Schroeder, P L; Birgisson, S; Slaughter, R L; Koehler, R E; Baker, M E
Abstract : Background: Intrasphincteric injection of botulinum toxin is a new treatment option for achalasia. Aims: To compare the immediate and long term efficacy of botulinum toxin with that of pneumatic dilatation. Methods: Symptomatic patients with achalasia were randomised to botulinum toxin (22 patients, median age 57 years) or pneumatic dilatation (20 patients, median age 56 years). Symptom scores were assessed initially, and at one, three, six, nine, and 12 months after treatment. Objective assessment included oesophageal manometry initially and at one month, and barium oesophagram initially and at one, six, and 12 months post-treatment. Results: Pneumatic dilatation resulted in a significantly (p=0.02) higher cumulative remission rate. At 12 months, 14/20 (70%) pneumatic dilatation and 7/22 (32%) botulinum toxin treated patients were in symptomatic remission (p=0.017). Failure rates were similar initially, but failure over time was significantly (p=0.01) higher after botulinum toxin (50%) than pneumatic dilatation (7%). Pneumatic dilatation resulted in significant (p<0.001) reduction in symptom scores, and lower oesophageal sphincter pressure, oesophageal barium column height, and oesophageal diameter. Botulinum toxin produced significant reduction in symptom scores (p<0.001), but no reduction in objective parameters. Conclusions: At one year pneumatic dilatation is more effective than botulinum toxin. Symptom improvement parallels objective oesophageal measurements after pneumatic dilatation but not after botulinum toxin treatment for achalasia.